Using health check data to investigate cognitive function in Aboriginal and Torres Strait Islanders living with diabetes in the Torres Strait, Australia. Issue 1 (24th September 2021) - Thompson, Fintan; Harriss, Linton R.; Russell, Sarah; Taylor, Sean; Cysique, Lucette A.; Strivens, Edward; Maruff, Paul; McDermott, Robyn
Abstract: Background: Type 2 Diabetes (T2DM) has a subtle deleterious effect on cognition and imposes a higher lifetime risk of cognitive impairment and dementia. In populations where both T2DM and dementia are highly prevalent, understanding more about the early effects of T2DM on cognition may provide insights into the lifetime risks of this disease. Methods: In 2016, 186 Australian Aboriginal and/or Torres Strait Islander residents of the Torres Strait (54% female, mean age =38.9 years, SD =15.9, range =15–74) participated in a community health check. The effect of diabetes (Type 1 or Type 2) on speed of thinking and working memory was assessed with the Cogstate Brief Battery (CBB) during the health check. Results: One third of participants had diabetes ( n = 56, 30.1%). After adjusting for age, education and previous iPad/Tablet experience, participants with diabetes had a small, yet significant reduction in accuracy on the One Back working memory task ( β = −.076, p = .010, r 2 = .042). The effect was most pronounced among participants with diabetes aged 20–49 years ( n = 20), who also had evidence of poorer diabetes control (eg HbA1c% ≥6.5, 76.6%), relative to participants with diabetes aged 50 years and over ( n = 31) (HbA1c% ≥6.5, 32.0%, p = .005). Conclusions: Early and subtle decrements in working memory may be a potential complication of diabetes among Aboriginal and Torres Strait Islander residents of the Torres Strait. Several potentially influential variables were not captured in this study (eg medication and diabetes duration). Greater preventative health resources are required for this population, particularly given the emerging elevated dementia rates linked to chronic disease. Abstract : In 2016, 186 Australian Aboriginal and/or Torres Strait Islander residents of the Torres Strait participated in a community health check, which included a cognitive assessment. The results suggest early and subtle decrements in working memory may be a potential complication of diabetes among Aboriginal and Torres Strait Islander residents of the Torres Strait.